Systematic Review of Factors Affecting Foster Parent Retention. Issue 3 (July 2021) - Hanlon, Ryan; Simon, June; Day, Angelique; Vanderwill, Lori; Kim, JaeRan; Dallimore, Elise
This study utilized the PRISMA protocol to conduct a systematic review of the literature published in the United States from 1989 to 2018 to identify factors that affect foster parent retention. Foster parent perception of their own limitations within the child welfare system, the child welfare system's ability to function fluidly, and the foster parents' relationship with the agency affects retention. In addition, the lack of material resources or inadequacy of funding to cover the cost of services for the child was identified as a barrier to retention. Personal attributes such as flexibility, confidence, and motivation contributed to the caregiver retention as did attending pre-service and in-service training, and having peer support from an experienced foster parent.